The Use of Art-Therapeutic Methods in the Work on the Formation of Communication Skills in Children With Autism Spectrum Disorders - E.E. Artemova; D.E. Belosvetova (Moscow State University of Psychology and Education, 2019)
The goal of the psychological and pedagogical experiment conducted in the academic year 2018-2019 is to determine the preferred sensory channels of preschool children with autism spectrum disorders for the development of recommendations on the use of art therapy methods and techniques in the formation of communication skills. The experimental group included 10 preschoolers from 4 to 7 years old with autism spectrum disorders. At the diagnostic stage, the degree of formation of communication skills was studied, the preferred sensory modalities were determined. All children showed a low level of development of communication skills: 2 of them had no speech, 4 of them used speech only in affectively significant situations, the rest used separate words and simple phrases for communication. According to the results of a experiment, it was determined that for 4 children the tactile channel is preferred, for 3 - visual, for 3 - audio. Recommendations are given on the use of art-therapeutic methods and techniques: for preschoolers with a predominant tactile way of perceiving - exercises with sand, for children with auditory preferences - music and dance therapy, for children with a predominant visual way of perceiving - isotherapy.